2005
DOI: 10.1021/es050022r
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Selected Pharmaceuticals in Subsurface Flow Constructed Wetlands:  A Pilot-Scale Study

Abstract: Subsurface flow constructed wetlands (SSFs) constitute a wastewater treatment alternative to small communities due to the low operational cost, reduced energy consumption, and no sewage sludge production. Although much information is available about conventional water quality parameters in SSF constructed wetlands, few data are available regarding specific contaminants. In this paper, we focus on the behavior of three widely used pharmaceuticals (clofibric acid, ibuprofen, and carbamazepine) in two pilot SSF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(66 citation statements)
references
References 36 publications
3
61
0
2
Order By: Relevance
“…This finding was attributed to the less anaerobic environment of the shallow wetland, which therefore had a less negative redox potential. 129,130 Of the PPCPs tested in these two studies, salicylic acid and carboxy-ibuprofene were removed at >80%, ibuprofen, hydroxyl-ibuprofen and naproxen at 50-80%, carbamazepine at <50%, whereas clofibric acid, ketoprofen and diclofenac were recalcitrant. Degradable PPCPs were removed by biodegradation, whereas musks were removed by adsorption onto the gravel bed.…”
Section: B4 Ppcp Transformation During Ozonationmentioning
confidence: 99%
“…This finding was attributed to the less anaerobic environment of the shallow wetland, which therefore had a less negative redox potential. 129,130 Of the PPCPs tested in these two studies, salicylic acid and carboxy-ibuprofene were removed at >80%, ibuprofen, hydroxyl-ibuprofen and naproxen at 50-80%, carbamazepine at <50%, whereas clofibric acid, ketoprofen and diclofenac were recalcitrant. Degradable PPCPs were removed by biodegradation, whereas musks were removed by adsorption onto the gravel bed.…”
Section: B4 Ppcp Transformation During Ozonationmentioning
confidence: 99%
“…Until now, available information on the performance of wetlands is mainly about general contaminant parameters, such as BOD 5 , nitrate nitrogen, and ortho-phosphate (U.S. EPA 1993; Belmont and Metcalfe 2003;Bezbaruah and Zhang 2003). However, some recent studies have focused on specific organic contaminants such as herbicides, pesticides, and pharmaceutical and personal care products (Matamoros et al 2005(Matamoros et al , 2007(Matamoros et al , 2008Matamoros and Bayona 2006;Schulz and Peall 2001;Schulz et al 2003;Rose et al 2006). Those studies highlighted the potential of wetlands as a risk-mitigation strategy for many water bodies polluted by organic contaminants.…”
Section: Background Aim and Scopementioning
confidence: 99%
“…The anti-inflammatory drug ibuprofen (IB) has shown to be readily removed in the three types of CWs (HF, VF and FWS). Results by Matamoros et al (2005) and Matamoros and Bayona (2006) show high removal efficiencies in HF wetlands (60 -80%), observing that the elimination rates are higher in shallower (0.27 m) than deeper beds (0.5 m). Matamoros et al (2008a) found a prevalence of OH-IB over Ca-IB metabolite in a HF wetland, which would be explained by its predominant aerobic biodegradation.…”
Section: Removal and Behavior Of Pharmaceuticals And Personal Care Prmentioning
confidence: 93%
“…and heavy metals, CWs have proven to have a great potential for the removal of EOCs. The existing literature includes mostly studies on the occurrence and behavior of pharmaceuticals at horizontal flow (HF) wetlands at micro and meso-scale (Matamoros et al, 2008a;Ávila et al, 2010;Hijosa et al, 2010b;Dordio et al, 2010;Hijosa et al, 2011b;Zhang et al, 2011;Reyes-Contreras et al, 2012;Zhang et al, 2012b;Ávila et al, 2013a), as well as pilot-scale (Matamoros and Bayona, 2006;Matamoros et al, 2005). Moreover, several studies have been carried out in vertical flow (VF) systems (Matamoros et al, 2007;Matamoros et al, 2009a;Song et al, 2009) and others at full-scale tertiary treatment systems, which include the use of a free water surface (FWS) wetland (Matamoros et al, 2008b;Llorens et al, 2009;Hijosa et al, 2010a;Matamoros and Salvadó, 2012).…”
Section: Introductionmentioning
confidence: 99%